INVERSI IMPEDANSI AKUSTIK MODEL BASED UNTUK KARAKTERISASI RESERVOAR DI LAPANGAN âXâ PADA FORMASI PLOVER BONAPARTE BASIN TIMOR SEA, TIMOR-LESTE - , FILOMENA DE JESUS ALVES ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Reservoir characterization in the field âXâ in the Bonaparte Basin has been carried out by analysis of impedance inversion to identify reservoir rock (sand). The main focus of this research is the reservoir sandstones (sand) in the Plover Formation with a model based method. The main data in seismic inversion is seismic data as input data and well data as the control data. In the study, using post-stack 2D seismic data, one well data, and two horizon. The horizon is the Top Plover Formation and Bottom Plover Formation. Based on the results of picking horizon are used to determine areas with high structure. From the results of inversion obtained impedance inversion value of the Plover Formation is 37000 â 44000 (ft/s)*(g/cc) for reservoir (sand) while 32500 â 37000 (ft/s)*(g/cc) for shale. From the results of the inversion then performed slice to determine the distribution of reservoir based acoustical impedance value is obtained. AN1 wells proved to be the prospect of being in the area and do not have closur lowly closed.